Spectrum Of Consumer Awareness In Islamic Finance: Takaful Industry In Malaysia - Nur I’ffah Muhammad Nasir; Rusni Hassan; Ahmad Zamri Osman (USIM Press, 2024)
Journal of Muamalat and Islamic Finance Research Volume 20 No.2 Page (125-134)